The Role of NF-κB/MIR155HG in Regulating the Stemness and Radioresistance in Breast Cancer Stem Cells - Yunbao Xu; Lu Yang; Guangming Li; Chuangzhou Rao (Frontiers in Bioscience-Landmark)
Background: Breast cancer stem cells (BCSCs) are instrumental in treatment resistance, recurrence, and metastasis. The development of breast cancer and radiation sensitivity is intimately pertinent to long non-coding RNA (lncRNA). This work is formulated to investigate how the lncRNA MIR155HG affects the stemness and radioresistance of BCSCs. Methods: Effects of MIR155HG knockdown on BCSCs were gauged in MCF-7 and MDA-MB-231 cell lines. MIR155HG expression was manipulated in cells, followed by an assessment of stemness, DNA damage repair, apoptosis, cell cycle, and the Wnt signaling pathway under radiation conditions. The interaction between nuclear factor kappa B (NF-κB) subunit RelA and MIR155HG was examined using a dual-luciferase reporter assay. To examine the binding interaction between RelA and MIR155HG promoter, chromatin immunoprecipitation was performed. Results: Breast cancer-derived stem cells exhibited a high level of MIR155HG. Knockdown of MIR155HG reduced stemness, enhanced radiosensitivity, induced apoptosis, and arrested cells in the G1 phase. Mechanistically, MIR155HG knockdown repressed Wnt/β-catenin signaling and mediated apoptosis-related protein expressions. NF-κB subunit RelA transcriptionally activated MIR155HG, thereby contributing to radioresistance in BCSCs. Conclusion: NF-κB regulates MIR155HG transcriptionally to activate the Wnt pathway, thus enhancing stemness and radioresistance in BCSCs. Targeting MIR155HG may enhance the susceptibility of cancer stem cells to radiation-induced cell death, potentially improving therapeutic outcomes. These findings underscore MIR155HG as a promising therapeutic target for breast cancer.